2021
DOI: 10.1177/2325967120985530
|View full text |Cite
|
Sign up to set email alerts
|

Noniatrogenic Medial Patellar Dislocations: Case Series and International Patellofemoral Study Group Experience

Abstract: Background: Most patellar dislocations occur in a lateral direction because of a summed lateral force vector and predisposing anatomic risk factors. Medial patellar instability is rare and is a well-recognized iatrogenic complication of an overly aggressive lateral retinacular release. Noniatrogenic medial patellar dislocations are rare. The management of these injuries is not well described. Purpose: To describe the experience of the International Patellofemoral Study Group with patients with noniatrogenic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Noniatrogenic medial patellar dislocation is extremely rare, and most patients with noniatrogenic medial patellar instability, such as those with EDS, demonstrate joint laxity. Loeb et al 11 . surveyed 47 members of the International Patellofemoral Study Group and reported that 3 of them had experienced only 6 cases of nonmedical medial patellar dislocation and 4 of these 6 cases were due to EDS.…”
Section: Discussionmentioning
confidence: 99%
“…Noniatrogenic medial patellar dislocation is extremely rare, and most patients with noniatrogenic medial patellar instability, such as those with EDS, demonstrate joint laxity. Loeb et al 11 . surveyed 47 members of the International Patellofemoral Study Group and reported that 3 of them had experienced only 6 cases of nonmedical medial patellar dislocation and 4 of these 6 cases were due to EDS.…”
Section: Discussionmentioning
confidence: 99%